A IMPLANTAÇÃO DE UM SISTEMA DE SEGURANÇA E SAÚDE OCUPACIONAL: UM ESTUDO DE CASO NA INDÚSTRIA DE MINERAÇÃO - Calixto, Eduardo (2004)
This report has as means objective to verify the subjects which take more influence in implantation of Safety and Health System, looking forward a specific case in Ore Industry, takes account the methodology of implantation, auditory results, reports, System s performance and Learning process, regarding management tools used in system implementation. Thereafter, its verify the influence of culture, resistance of change and learning process in implementation of system. By this way, it ll introduced the Safety and health System model of Companhia Vale do Rio Doce based in OHSAS 18001 standard and it s element s , the fourteen managements tools and implementation methodology which permit take some conclusions about case study in a Operational pelotization management.